Pengaruh Citra Destinasi dan Electronic Word of Mouth Terhadap Minat Berkunjung Pada Wisata Pantai Tambakrejo Blitar - Aziza, Umma Latifa Nur; Purwanto, Sugeng (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Purpose of this research was to determine the effect of Destination Image and Electronic Word of Mouth on Tourist Visiting Interests on Tambakrejo Beach tourism in Blitar. This research used a quantitative approach. Nonprobability sampling method with purposive sampling technique was used for sampling with research samples obtained as many as 90 respondents. Types primary data is used in this research. Data processing is done by using Partial Least Square (PLS) analysis technique. Results of research showed that: 1) Destination Image had a significant positive effect on Tourist Visiting Interests at Tambakrejo Beach Blitar. 2) Electronik Word of Mouth has a significant positive effect on Turist Visiting Interests at Tambakrejo Beach Blitar.